INTERDISCIPLINARY APPROACH IN METHODOLOGY OF SPORT DISCIPLINES TEACHING TO THE FUTURE P.E. SPECIALISTS - Dzhurynskyі, Petrо B. (Educological discourse, 2015)
The aim of the research was to determine the peculiarities of teaching methods of sports disciplіnes in future PE specialists’ training concerning the interdisciplinary integration. On ascertaining stage of the experiment, the ratio of the experimental group students with the knowledge of educational material on professional sports disciplines and practical training cycle in both the control and the experimental group was characterized as low. The results of the final cut-off figures have found out that the future PE teachers’ training in the interdisciplinary integration of sports disciplines has optimized the educational process. In the experimental group, the index of learning and indicators of motivation to use interdisciplinary integration of sports disciplines have significantly improved in contrast to the control group.